A mystery to be solved: perceptions of academic writing in the initial teacher training of primary school teachers (Praxis Educativa, 2025)
In this article we conduct an analysis of the meanings that professors and students produce daily when dealing with academic writing at a teacher training institute located in the western region of the Metropolitan Area of Buenos Aires. We adopt a sociocultural perspective on written language from the New Literacy Studies, and through an ethnographic approach, we inquire into how students in a Primary Education Teacher Training Program understand the reading and writing demands posed by their professors, as well as the discourses on writing and its teaching that the professors align with when assessing the students’ use of written language during their initial teacher education. We denote that academic writing appears to be at the center of a deep gap between professors and students: professors simultaneously attribute students’ difficulties in reading and writing to a lack of skills in constructing grammatically correct texts, ignorance of the literacy practices specific to the academic field, and the manner in which the students’ relationship with written language is shaped by identity and epistemology, whereas students tend to assume that the reading and writing requirements of teacher education pose a sort of mystery to be solved and are the mere result of idiosyncratic traits and personal quirks of the professors.
Keywords: Reading and writing in higher education; Academic literacy; New Literacy Studies; Teacher training; Ethnography